1968 e a teoria social contemporânea, 50 anos depois: rebelião social, fragmentação ou nova cultura política? - Almada, Pablo Emanuel Romero [UNESP] (Programa de Pós-Graduação em Sociologia - UFRGS, 2020)
This article investigates how the events of 1968 resonated in Contemporary Sociological Theory, considering the 50-year anniversary of these events. In this sense, 1968 has been understood as an event of significant effects throughout the world, led initially by the students’ movement, and which encompasses schisms in radicalism, new political-ideology configurations, criticism of Soviet socialism and the opening of a Third-World perspective in social struggles. Therefore, the event served as a basis for reflection for several theoretical formulations of Marxism, critical theory, structuralism, poststructuralism, and postmodern currents, each with its specific interpretation of the facts. By grouping these interpretations, three distinct approaches in sociological theory about these events emerge: rebellion, social fragmentation, and a new political culture of social movements. Therefore, as a reading hypothesis, we grouped the three interpretative perspectives, which fulfill a preliminary identification of the analyses performed in the last 40 years. Thus, we aim to construct a broad historical and sociological survey, in regard to the understanding of the events of 1968, focusing on how they resonate in the theoretical developments of the last decades. This survey also aims to investigate how the recent disputes around the meanings of the 1968 conflicts are presented in the “celebrations” of the 50-year anniversary, leading to disputes of affirmation and denial of the meanings of events in sociological theory.

O artigo investiga as ressonâncias dos eventos de 1968 na Teoria Sociológica Contemporânea, considerando os 50 anos dos ocorridos. Nesse sentido, 1968 foi entendido como um evento de significativos efeitos pelo globo, protagonizado inicialmente pelo movimento estudantil e que engloba cisões no radicalismo, novas configurações político-ideológicas, a crítica ao socialismo soviético e a abertura de uma perspectiva terceiro-mundista nas lutas sociais. Por isso, o evento serviu de base de reflexão para várias formulações teóricas do marxismo, da teoria crítica, do estruturalismo, do pós-estruturalismo e de correntes pós-modernas, cada qual com uma interpretação específica. Agrupando tais interpretações, encontram-se três abordagens distintas na teoria sociológica sobre os eventos: rebelião, fragmentação social e nova cultura política dos movimentos sociais. Portanto, como hipótese de leitura, agrupamos as três perspectivas interpretativas, as quais cumprem de forma geral uma identificação preliminar das análises realizadas nos últimos 40 anos. Assim, objetiva-se a construção de um amplo balanço histórico e sociológico no que diz respeito à sua compreensão dos acontecimentos de 1968, com enfoque na ressonância desses na elaboração teórica das últimas décadas. Esse balanço almeja investigar também como as disputas recentes em torno dos sentidos dos conflitos de 1968 se apresentam nas “comemorações” de 50 anos, ensejando as disputas de afirmação e negação dos sentidos dos acontecimentos na teoria sociológica.
1968 and contemporary social theory 50 years later: social rebellion, fragmentation, or a new political culture?
Keywords: 1968; students’ movements; political culture; contemporary social theory; history of the present time; 1968; movimento estudantil; cultura política; teoria social contemporânea; história do tempo presente